Effect of health resort rehabilitation on pain intensity and hip range of motion in patients with coxarthrosis - Trybulec, Bartosz; Wyszyńska, Małgorzata (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Due to increase of the average lifespan of Polish society there is a high susceptibility to primary and secondary degenerative diseases of the large joints of the lower limbs. One of widely used therapeutic methods is health resort rehabilitation that includes various physiotherapeutic methods. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim: The aim of the study was to evaluate an effect of health resort rehabilitation on pain intensity and change the ranges of motion in the hip joint in coxarthrosis depending on age and sex of examined persons. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method: The research material consisted of a group of 50 patients (34 women and 16 men) examined before the start of rehabilitation and three weeks after its completion. The study used a questionnaire of our own design, comprising subjective questionnaire, VAS scale, WOMAC questionnaire and measurement form in SFTR system. Physiotherapy proceedings included: kinesitherapy, physiotherapy, balneotherapy and prophylaxis. Afterwards obtained results underwent statistical analysis using nonparametric tests. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: The results of the studies showed statistically significant differences in pain intensity, occurring restrictions of movement in the hip joint and the difficulties in the functioning of physical and mental health.